2018
DOI: 10.1186/s13638-018-1033-5
|View full text |Cite
|
Sign up to set email alerts
|

Mining shopping data with passive tags via velocity analysis

Abstract: Unlike online shopping, it is difficult for the physical store to collect customer shopping data during the process of shopping and conduct in-depth data mining. The existing methods to solve this problem only considered how to collect and analyze the data, but they have not paid attention to the large computation amount, bulk data amount, and long time delay, in which they can not feedback user data timely and effectively. In this paper, we present the received signal strength of passive radio frequency ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…As for the study of exploration shopping data with passive tags via speed analysis, (Zhao et al, 2018), it confirmed that it is difficult for the actual store to collect customer shopping data during the shopping process and to conduct deep data exploration operations, as opposed to online shopping. The current methods of solving this problem concern only how data is collected and analyzed, but it does not care about the large amount of account, the amount of collected data and the long delay, as it cannot provide user feedback in a timely and effective manner.…”
Section: Literature Reviewmentioning
confidence: 91%
“…As for the study of exploration shopping data with passive tags via speed analysis, (Zhao et al, 2018), it confirmed that it is difficult for the actual store to collect customer shopping data during the shopping process and to conduct deep data exploration operations, as opposed to online shopping. The current methods of solving this problem concern only how data is collected and analyzed, but it does not care about the large amount of account, the amount of collected data and the long delay, as it cannot provide user feedback in a timely and effective manner.…”
Section: Literature Reviewmentioning
confidence: 91%
“…Specifically, it uses RFID technology to capture interactions of customers with products in a store (e.g., picking up products from a shelf). Similarly, Zhao et al [29] use RFID technology to identify products that are popular among customers, as well as products that are correlated with each other. Additionally, they use their collected data to find store areas that are highly frequented (i.e., hot zones), which enables retailers to optimize their store layouts.…”
Section: Related Workmentioning
confidence: 99%
“…the winner takes all. To solve the problem, the psych package of the R language was employed to obtain the descriptive value of each index whose distribution skews to the left [18]. Then, the bcPower function was called from the car package of R language to reduce the skewness of the skewed distributions.…”
Section: Data Processing and Index Selectionmentioning
confidence: 99%